The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph18147305
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prognostic Factors for Palatal Fistulae after Cleft Lip and Palate Surgery in a North-Western Romanian Population over a 10-Year Period

Abstract: Cleft lip and palate is the most frequent birth anomaly, with increasing reported rates of complications, such as palate fistulae. Current studies concerning the occurrence rate of cleft lip and palate (CLP) report 2 to 10 cases in 10,000 births. The purpose of this study was to investigate the existence of factors that could predict the occurrence of fistulae after cleft lip and palate surgery. A retrospective study was performed by collecting and analyzing data from all patients who were operated for cleft l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
1
2
Order By: Relevance
“…Severity of clefting, comorbid cleft lip, and Veau category of cleft have shown to themselves as some of the more predictive metrics of a patient's postoperative course. 24,25 The present study did not find a significant relationship between presence of comorbid cleft lip and need for surgery to correct VPI = 0.057). A 2-stage palate repair was associated with a significantly elevated need for surgery to correct VPI compared with a Furlow palatoplasty.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Severity of clefting, comorbid cleft lip, and Veau category of cleft have shown to themselves as some of the more predictive metrics of a patient's postoperative course. 24,25 The present study did not find a significant relationship between presence of comorbid cleft lip and need for surgery to correct VPI = 0.057). A 2-stage palate repair was associated with a significantly elevated need for surgery to correct VPI compared with a Furlow palatoplasty.…”
Section: Discussioncontrasting
confidence: 59%
“…Comorbid cleft lip was associated with a significantly higher rate of oronasal fistula development following primary palatoplasty. Severity of clefting, comorbid cleft lip, and Veau category of cleft have shown to themselves as some of the more predictive metrics of a patient's postoperative course 24,25 . The present study did not find a significant relationship between presence of comorbid cleft lip and need for surgery to correct VPI ( P = 0.057).…”
Section: Discussioncontrasting
confidence: 59%
“…Patient's developmental age at the time of repair (coded ToR) was the only other variable that showed significant positive correlation to the occurrence of ONF in this study. Although this observation has been contradicted by a recent study [26] which observed that timing of surgery made no difference to fistula development, the authors' observation arose from a dichotomy of patients into age groups < 4 years vs >4 years. This categorisation is at variance with what we did in this study whereby patients were grouped by their developmental milestones into infant, toddler, preschooler, school age and adolescents.…”
Section: Discussionmentioning
confidence: 74%